Visual Spectroscopy and Colour Modelling for Nondestructive Quality Evaluation of Apple - Jha, S N; Rai, D R; Gunasekaran, S (Journal of Agricultural Engineering, 2010)
Potential of visual spectroscopy and colour data obtained using simple handheld colourimeter was investigated for nondestructive prediction of two important internal quality parameters of apple: total soluble solids (TSS, degree Brix) and titrable acidity (TA). Apple colour in terms of Hunter lab L, a, b values and visual spectral (400 to 700 nm) reflectance values of five cultivars were determined. Empirical models were fitted to L, a, b values and partial least squares and multiple linear regression models were fitted to spectral reflection data. The model predictions were validated via full-cross validation technique. Statistical analyses of the results indicate that TA is better predicted than TSS or TA/TSS ratio using colour values. The models based on colour values are better than those using spectral reflectance data. A linear model with colour parameters a, b and aÂ² fitted the experimental TA values with R values of 0.767 and 0.679 for calibration and validation, respectively.